1927 R.I. Pub. Laws 256, ch. 1052, §§ 1, 3 - (:unkn) unknown (My University, 1927)
Prohibited a person who has previously been convicted of a violent crime from owning, carrying, or possessing any firearm (including machine gun or pistol).
Keywords: POSSESSION - DANGEROUS PERSONS